2012
DOI: 10.1016/j.foreco.2011.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Local habitat and landscape affect Ixodes ricinus tick abundances in forests on poor, sandy soils

Abstract: A large fraction of the forests in northern Belgium consists of homogeneous pine stands on nutrientpoor and acid sandy soils. However, in common with many other parts of Europe, the current forest management aims at increasing the share of deciduous and mixed forests. This might create favourable habitats for the tick Ixodes ricinus, which is Europe's main vector of Borrelia burgdorferi sensu lato, the causative agent of Lyme borreliosis in humans. Considering the threat to human health, it is important to kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 62 publications
3
61
0
2
Order By: Relevance
“…Além destes fatores, condições ambientais específicas produzidas pelo processo de fragmentação de habitats parecem ser capazes de influenciar a distribuição agregada de carrapato (Tack et al 2012). No estudo realizado por Tack et al (2012), foi observado uma maior abundância de carrapatos em fragmentos com maiores habitats de borda.…”
Section: Discussionunclassified
“…Além destes fatores, condições ambientais específicas produzidas pelo processo de fragmentação de habitats parecem ser capazes de influenciar a distribuição agregada de carrapato (Tack et al 2012). No estudo realizado por Tack et al (2012), foi observado uma maior abundância de carrapatos em fragmentos com maiores habitats de borda.…”
Section: Discussionunclassified
“…Some studies have shown a correlation between tick abundance and the environment (ARZUA, 2007;JAENSON et al, 2009;TACK et al, 2012). However, whatever differences are found appear to be more related to the presence of hosts than to the actual structure of the landscape (ESTRADA-PEÑA, 2003;ALLAN et al, 2003;BROWNSTEIN et al, 2005;TACK et al, 2012).…”
Section: Palavras-chave: Amblyomma Brasiliense Amblyomma Cajennensementioning
confidence: 99%
“…Because forest areas may differ from open habitats such as grasslands, in terms not only of vegetation type but also weather patterns (ARZUA, 2007;TACK et al, 2012), an analysis was also made of the abundances of species found as a function of micro-and mesoclimatic conditions. Curió Municipal Nature Park (Curió Park) (22°33' -22°36' S and 43°40' -43°43' W) is a Full Protection Conservation Unit, located in the municipality of Paracambi, Rio de Janeiro state, Brazil.…”
Section: Palavras-chave: Amblyomma Brasiliense Amblyomma Cajennensementioning
confidence: 99%
See 2 more Smart Citations